2005
DOI: 10.1086/430953
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variations in the Receptor‐Ligand PairCCR5andCCL3L1Are Important Determinants of Susceptibility to Kawasaki Disease

Abstract: Kawasaki disease (KD) is an enigmatic, self-limited vasculitis of childhood that is complicated by development of coronary-artery aneurysms. The high incidence of KD in Asian versus European populations prompted a search for genetic polymorphisms that are differentially distributed among these populations and that influence KD susceptibility. Here, we demonstrate a striking, inverse relationship between the worldwide distribution of CCR5- Delta 32 allele and the incidence of KD. In 164 KD patient-parent trios,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
64
0
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 39 publications
5
64
0
3
Order By: Relevance
“…In previous studies, we found that the copy number of CCL3L1 modified the Kawasaki disease-, SLE-and HIV-1-disease-influencing effects of CCR5 haplotypes (Burns et al, 10 Mamtani et al 11 and data not shown). Thus, here we sought to determine whether the underlying copy number of CCL3L1 modified the SLE-and SS-influencing effects associated with FCGR3B CNVs.…”
Section: Modifier Effects Of Ccl3l1 In Sle and Primary Ssmentioning
confidence: 67%
See 1 more Smart Citation
“…In previous studies, we found that the copy number of CCL3L1 modified the Kawasaki disease-, SLE-and HIV-1-disease-influencing effects of CCR5 haplotypes (Burns et al, 10 Mamtani et al 11 and data not shown). Thus, here we sought to determine whether the underlying copy number of CCL3L1 modified the SLE-and SS-influencing effects associated with FCGR3B CNVs.…”
Section: Modifier Effects Of Ccl3l1 In Sle and Primary Ssmentioning
confidence: 67%
“…[1][2][3][4] It is to be noted that there seems to be an enrichment of CNV in immune response genes 1 such that they may contribute to the observed inter-individual variability in susceptibility to infectious diseases, vasculitis and autoimmune diseases. For example, we and others found that the copy number of segmental duplication on chromosome 17q that contains the gene encoding the chemokine CC chemokine ligand 3-like 1 (CCL3L1) influences HIV-AIDS susceptibility, [5][6][7][8][9] and the risk of developing Kawasaki's disease, 10 systemic lupus erythematosus (SLE) 11 and rheumatoid arthritis (RA). 12 CNV in the gene encoding the complement component C4 and FCGR2C has been associated with SLE 13 and idiopathic thrombocytopenic purpura, 14 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Burns et al [15] have also reported about genetic variation in CCR5 and susceptibility to KD, demonstrating an inverse relationship between the worldwide distribution of CCR5-D32 allele and the incidence of KD. In a large familybased study using transmission disequilibrium test (TDT) analyses, an asymmetric transmission of the CCR5-D32 allele from 46 heterozygous parents to their affected children is observed, supporting the hypothesis that the CCR5-D32 allele might protect against development of KD.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, in European populations the average allele frequency is estimated to be 10%, whereas in Asian populations the 32-bp deletion is rare [14]. Moreover, Burns et al report about a striking, inverse relationship between the worldwide distribution of the CCR5-D32 allele and the incidence of KD [15]. They state that genetic variation in CCR5 plays an influential role in KD susceptibility but that the results need to be confirmed in an independent cohort.…”
Section: Introductionmentioning
confidence: 99%
“…This triggered activation, in turn, starts a systemic immune response leading to uncontrolled inflammation and vasculitis in genetically susceptible patients (9)(10)(11). Although a number of previous studies have sought to determine the cause of this disease, very few have addressed the role of the different peripheral T-cell populations in the acute phase of KD or in the effectiveness of IVIG treatment (12,13).…”
mentioning
confidence: 99%